Single-cell detection of primary transcripts, their genomic loci and nuclear factors by 3D immuno-RNA/DNA FISH in T cells - Salataj, Eralda; Spilianakis, Charalampos G.; Chaumeil, Julie (Frontiers in Immunology, 2023)
Over the past decades, it has become increasingly clear that higher order chromatin folding and organization within the nucleus is involved in the regulation of genome activity and serves as an additional epigenetic mechanism that modulates cellular functions and gene expression programs in diverse biological processes. In particular, dynamic allelic interactions and nuclear locations can be of functional importance during the process of lymphoid differentiation and the regulation of immune responses. Analyses of the proximity between chromatin and/or nuclear regions can be performed on populations of cells with high-throughput sequencing approaches such as chromatin conformation capture (“3C”-based) or DNA adenine methyltransferase identification (DamID) methods, or, in individual cells, by the simultaneous visualization of genomic loci, their primary transcripts and nuclear compartments within the 3-dimensional nuclear space using Fluorescence In Situ Hybridization (FISH) and immunostaining. Here, we present a detailed protocol to simultaneously detect nascent RNA transcripts (3D RNA FISH), their genomic loci (3D DNA FISH) and/or their chromosome territories (CT paint DNA FISH) combined with the antibody-based detection of various nuclear factors (immunofluorescence). We delineate the application and effectiveness of this robust and reproducible protocol in several murine T lymphocyte subtypes (from differentiating thymic T cells, to activated splenic and peripheral T cells) as well as other murine cells, including embryonic stem cells, B cells, megakaryocytes and macrophages.